Evaluation ecological niche between Platyceps rhodorachis and P. karelini (Serpentes: Colubridae) in Iran - Seyed Hassan Moradi; Eskandar Rastegar Pouyani; saeed hosseinian; Jamil Zargan (Iranian Journal of Animal Biosystematics, 2021)
Platyceps rhodorachis (JAN, 1863) and P. karelini (BRANDT, 1838) are both members of the P. rhodorachis complex species, which is widely distributed in Iran and includes many local populations in the country. These two species are molecularly and to some extent morphologically valid. However, hybrids between P. karelini and P. rhodorachis have been described, but so far their ecological differentiation have not been evaluated. In this study, the ecological niche models was predicted for these two members of the P. rhodorachis complex using bioclimatic layers and geographical coordinates. Possible habitat models show the distribution density of these two species in the southern (including some islands in the Persian Gulf) regions, and some areas in northeastern Iran. The results of niche similarity tests (identity and niche overlap tests) based on the criteria of environmental species, in order to assess the degree of species differentiation, indicate the degree of differentiation between these two sister species and raises the possibility of a hybrid belt in southern Iran.